Overcoming Chemoresistance: Altering pH of Cellular Compartments by Chloroquine and Hydroxychloroquine - Halcrow, Peter W.; Geiger, Jonathan D.; Chen, Xuesong (Frontiers in Cell and Developmental Biology, 2021)
Resistance to the anti-cancer effects of chemotherapeutic agents (chemoresistance) is a major issue for people living with cancer and their providers. A diverse set of cellular and inter-organellar signaling changes have been implicated in chemoresistance, but it is still unclear what processes lead to chemoresistance and effective strategies to overcome chemoresistance are lacking. The anti-malaria drugs, chloroquine (CQ) and its derivative hydroxychloroquine (HCQ) are being used for the treatment of various cancers and CQ and HCQ are used in combination with chemotherapeutic drugs to enhance their anti-cancer effects. The widely accepted anti-cancer effect of CQ and HCQ is their ability to inhibit autophagic flux. As diprotic weak bases, CQ and HCQ preferentially accumulate in acidic organelles and neutralize their luminal pH. In addition, CQ and HCQ acidify the cytosolic and extracellular environments; processes implicated in tumorigenesis and cancer. Thus, the anti-cancer effects of CQ and HCQ extend beyond autophagy inhibition. The present review summarizes effects of CQ, HCQ and proton pump inhibitors on pH of various cellular compartments and discuss potential mechanisms underlying their pH-dependent anti-cancer effects. The mechanisms considered here include their ability to de-acidify lysosomes and inhibit autophagosome lysosome fusion, to de-acidify Golgi apparatus and secretory vesicles thus affecting secretion, and to acidify cytoplasm thus disturbing aerobic metabolism. Further, we review the ability of these agents to prevent chemotherapeutic drugs from accumulating in acidic organelles and altering their cytosolic concentrations.